PENDAMPINGAN BTQ PADA SANTRI PONDOK PESANTREN NURUL HUDA BAETURROHMAN DALAM MENINGKATKAN KUALITAS BACAAN AL-QUR'AN DI DESA CILILIN KECAMATAN CILILIN - Mohammad Sabarudin (Jurnal Al Maesarah, 2022)
Cililin is a sub-district located in West Bandung Regency, West Java with the northern border, the village bordering the South Mekar Mukti Village, the village bordering the West Batu Layang Village. Cililin has always been known as the Gudang Santri and Pabrik Haji. However, along with the times, the nickname Gudang Santri and Pabrik Haji is fading because Islamic cultural norms are increasingly being eroded by the times, especially the global epidemic Covid-19 that has hit all levels of society in various spheres of  life, one of which is the religious realm. This is based on one of the reasons for the decline in the quality of reading the Qur'an for students at one of the Islamic boarding schools in Cililin Village, West Bandung. This study uses an independent Community Service Program mentoring method, where the number of respondents is 10 students. The results of Community Service are; an increase in the quality of reading the Koran of students. Conclusion: BTQ assistance to adolescent students at the Baeturrohman Islamic Boarding School has a positive impact on increasing the quality of reading the Qur'an.